2003
DOI: 10.1093/jaoac/86.2.296
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration of Total Yeasts and Molds in Foods by the SimPlate® Yeast and Mold–Color Indicator Method and Conventional Culture Methods: Collaborative Study

Abstract: The relative effectiveness of the SimPlate Yeast and Mold-Color Indicator method (Y&M–CI) was compared to the U.S. Food and Drug Administration's (FDA) Bacteriological Analytical Manual (BAM) method and the proposed International Organization for Standardization (ISO) method, ISO/CD 21527, for enumerating yeasts and molds in foods. Test portions were prepared and incubated according to the conditions stated in both the BAM and ISO methods. Six food types were analyzed: frozen corn dogs, nut meats, frozen f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Enumerators would be trained for the express purpose of conducting microbiological challenge tests, proficient in water quality testing methods including aseptic technique. They would use established field water quality testing methods to process influent and effluent water samples resulting from the field challenge test, such as field membrane filtration to enumerate E. coli 64,65 , and SimPlate method for Yeast and Mold Color Indicator (Y&M-CI) for the detection and quantification of yeast 68 , which has been validated for use against conventional agar plating methods 69,70 and is appropriate for low-resource field contexts due to the pre-packaged sterile materials it uses, as well as the lack of requirement for reagent refrigeration 68 .…”
Section: Useful Applications Of the Field Challenge Test Methodsmentioning
confidence: 99%
“…Enumerators would be trained for the express purpose of conducting microbiological challenge tests, proficient in water quality testing methods including aseptic technique. They would use established field water quality testing methods to process influent and effluent water samples resulting from the field challenge test, such as field membrane filtration to enumerate E. coli 64,65 , and SimPlate method for Yeast and Mold Color Indicator (Y&M-CI) for the detection and quantification of yeast 68 , which has been validated for use against conventional agar plating methods 69,70 and is appropriate for low-resource field contexts due to the pre-packaged sterile materials it uses, as well as the lack of requirement for reagent refrigeration 68 .…”
Section: Useful Applications Of the Field Challenge Test Methodsmentioning
confidence: 99%
“…The plates were incubated at 35C for 24 h prior to counting coliforms (purple-red colonies) and E. coli (fluorescent colonies under long-wave UV light). Enumeration of coliforms and E. coli using the SimPlate CEc-CI method with multiple test medium (BioControl System) was performed according to the manufacturer's instructions and procedures of Feldsine et al (2005). The total number of positive wells for coliforms was counted on the basis of color change.…”
Section: Enumeration Of Coliforms and E Colimentioning
confidence: 99%
“…Several studies have indicated that the SimPlate CEc-CI method is comparable to other methods, and is a suitable alternative for detection and enumeration of total coliforms and E. coli in foods Russel 2000;Lee and Lewis 2003). The SimPlate CEc-CI method has recently been approved by the Research Institute of the AOAC, Method 2005.3 (Feldsine et al 2005). Nevertheless, information on the efficacy of the SimPlate methods for use in environmental farm samples is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, harmful effects as spoilage of meat, reduced shelf-life of meat and public health hazard, as infection or intoxication, are the main sequalae of microbially contaminated meat (Eley, 1992;Park et al, 2015). Similarly, fungi occur in meat and meat products could cause various degrees of spoilage and/or render the affected meat hazardous by the production of mycotoxins (Feldsine et al, 2003;Ismail et al, 1995).…”
Section: Introductionmentioning
confidence: 99%